A Single Mass Forming Colonic Primary Mantle Cell Lymphoma. (4th August 2016) - Daniel, Fady; Assi, Hazem I.; Karaoui, Walid; El Cheikh, Jean; Bannoura, Sami; Nassif, Samer
Abstract : Mantle cell lymphoma (MCL) is a subtype of non-Hodgkin's lymphoma (NHL) comprising around 7% of adult NHL. It is characterized by a chromosomal translocation t(11:14) and overexpression of Cyclin D1. The incidence of secondary gastrointestinal tract involvement in MCL ranges from 10 to 28% in various series. However primary gastrointestinal MCL is very rare, accounting for only 1 to 4% of primary gastrointestinal lymphomas. The most common endoscopic feature of primary intestinal MCL is multiple lymphomatous polyposis. In rare cases it presents as protruded lesions or superficial lesions. Single colonic mass presentation is an extremely infrequent presentation. MCL has an aggressive course with quick progression, and most cases are discovered in the advanced stages. Colonic biopsies with histologic examination and specific immunohistochemical staining are the gold standard for a proper diagnosis. We report a case of a single mass forming mantle cell lymphoma of the ascending colon in a 57-year-old female patient with unusual colonoscopic and radiologic features and describe the therapy the patient received, thereby adding to the spectrum of clinical presentations of this aggressive lymphoproliferative disorder.